2019
DOI: 10.4103/jmas.jmas_7_18
|View full text |Cite
|
Sign up to set email alerts
|

Robotic-assisted minimally invasive oesophagectomy for cancer: An initial experience

Abstract: Adequate experience in TLE can help minimally invasive surgeons in easy adoption of RAMIE with satisfactory outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Twenty studies reported total inpatient LoS of < 10 days; none of these studies used an open approach for the thoracic or abdominal phases. 25 , 41 , 43 , 44 , 52 , 56 69 In comparison, 27 studies reported total LoS > 14 days, of which six used an open approach in either the abdominal or thoracic phases. 5 , 24 , 25 , 33 , 42 , 45 , 46 , 55 , 70 85 This indicates the robotic and conventional minimally invasive approaches are associated with shorter LoS, however clinical trials are required to validate this.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Twenty studies reported total inpatient LoS of < 10 days; none of these studies used an open approach for the thoracic or abdominal phases. 25 , 41 , 43 , 44 , 52 , 56 69 In comparison, 27 studies reported total LoS > 14 days, of which six used an open approach in either the abdominal or thoracic phases. 5 , 24 , 25 , 33 , 42 , 45 , 46 , 55 , 70 85 This indicates the robotic and conventional minimally invasive approaches are associated with shorter LoS, however clinical trials are required to validate this.…”
Section: Discussionmentioning
confidence: 99%
“…In four studies, a stapled esophagogastric anastomosis was formed within the cervical wound to restore continuity of the digestive tract. 42 , 44 , 46 , 115 In comparison, two studies reported a hand-sewn anastomosis—one formed using the robotic platform and one extracorporeal. 42 , 115 The reported AL rate was higher among those who underwent three-stage esophagectomy (12.5%) compared with two-stage (8.10%).…”
Section: Discussionmentioning
confidence: 99%